2015
DOI: 10.1037/a0038319
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Jaakkola (2014): “Do animals understand invisible displacement? A critical review”.

Abstract: Jaakkola (2014) critiques studies that investigate nonhuman capacities to track objects undergoing invisible displacements. She states that the results of most of these studies are tainted by cuing, that conceptual understanding is lacking, and that, as a consequence, great apes are the only nonhumans to have full Stage 6 object permanence. Any critique, however, must clearly take into account all published information on the techniques being used, including more recent data that counter its negative claims. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Jaakkola (2014) made the basic methodological observation that in order to be certain an animal was tracking the invisible displacement of an object, it was essential that the animal could not directly perceive that object by any sensory modality at the time of search. Pepperberg (2015) responds by noting that olfaction is not strong enough in parrots to allow them to solve these tasks, that nonfood items were sometimes used in the invisible displacement studies, and that control trials in a later study found that parrots were at chance with an olfactory cue. Therefore, “Olfactory cues should not be an issue of concern in the specific object permanence studies cited and should not affect the conclusions.” This response left me puzzled, because we are in complete agreement.…”
Section: Olfactory Cuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Jaakkola (2014) made the basic methodological observation that in order to be certain an animal was tracking the invisible displacement of an object, it was essential that the animal could not directly perceive that object by any sensory modality at the time of search. Pepperberg (2015) responds by noting that olfaction is not strong enough in parrots to allow them to solve these tasks, that nonfood items were sometimes used in the invisible displacement studies, and that control trials in a later study found that parrots were at chance with an olfactory cue. Therefore, “Olfactory cues should not be an issue of concern in the specific object permanence studies cited and should not affect the conclusions.” This response left me puzzled, because we are in complete agreement.…”
Section: Olfactory Cuesmentioning
confidence: 99%
“…Jaakkola (2014) argued that because the majority of studies of animals’ understanding of invisible displacement did not adequately control for the use of alternative lower-level strategies, clear and solid evidence for a conceptual understanding of invisible displacement existed only for great apes. Pepperberg (2015) takes issue with this conclusion with respect to Grey parrots. While I agree that olfactory and social cueing may not be issues of concern for parrots, I reiterate the need for a study that adequately controls for associative learning before we can confidently claim that parrots understand invisible displacement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects have to track the visible trajectory of the device containing the object. These tasks have been solved by children 79 , corvids 1012 , psittacines 1317 , and great apes 1821 , although it remains unclear whether any species other than humans and the great apes have succeeded in these tasks using mental representation, rather than simpler associative learning strategies 20,22 ; but see 23 . Nevertheless, there is convincing evidence that several species, including dogs, monkeys, parrots, corvids, and chickens can represent object identity in other tasks 13,2431 , and chickens have also been shown to represent trajectory, correctly predicting the end-destination of an object behind one of two screens 3234 .…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, others have argued that the performance of dogs (e.g., Gagnon & Doré, 1992, 1993, 1994; Pasnak, Kurkjian, & Triana, 1988) can be explained by low-level associative rules rather than an understanding of object concepts (Collier-Baker et al, 2004; Fiset & LeBlanc, 2007). In a reply, Pepperberg (2015) refuted Jaakkola’s critique and argued that the literature provides sufficient evidence to show that Gray parrots demonstrate full object permanence.…”
mentioning
confidence: 99%